An updated checklist of Clupeiformes (Teleostei) from Indian waters, with distribution and conservation status - Pillai, Honey Unnikrishna; Dutta, Sayani; Saren, Saresh Chandra; K.g., Vimal Kumar; P., Vinod; Raghunathan, Chelladurai (Zootaxa, 2026)
The present study provides an updated checklist and distributional analysis of clupeiform fishes from Indian waters based on published literature, online databases, and fish landing records. Clupeiform fishes are predominantly pelagic, schooling, and filter-feeding forms widely distributed in marine, estuarine, and freshwater ecosystems, and constitute an important component of global pelagic fishery resources. In India, this group contributes substantially to marine fish landings and supports major coastal fisheries, with several species subjected to intensive exploitation due to their high commercial and nutritional value. The present compilation includes a total of 97 valid species of the order Clupeiformes belonging to 26 genera and seven families recorded from Indian waters, representing approximately 21.1% of the global species diversity and 31.3% of the known genera of the order, which currently comprises ten families worldwide. Among the recorded families, Engraulidae and Dorosomatidae are the most species-rich, whereas Chirocentridae and Spratelloididae contain fewest species. The Bay of Bengal exhibits the highest species richness, followed by the Arabian Sea, while the Andaman & Nicobar Islands and Lakshadweep Islands are comparatively less diverse. Assessment based on the IUCN Red List indicates that 56 species are listed as Least Concern, 32 as Data Deficient, eight as Not Evaluated, and one species falls under vulnerable category. This compiled checklist serves as a foundational reference for future investigations into the taxonomy, biodiversity, and conservation of Indian clupeiform fishes.